Molecular evidence for the involvement of cotton GhGLP2, in enhanced resistance to Verticillium and Fusarium Wilts and oxidative stress - Pei, Yakun (Sci Rep, 2020)
Germin-like proteins (GLPs) are a diverse and ubiquitous family of plant glycoproteins belonging to the cupin super family; they play considerable roles in plant responses against various abiotic and biotic stresses. Here, we provide evidence that GLP2 protein from cotton (Gossypium hirsutum) functions in plant defense responses against Verticillium dahliae, Fusarium oxysporum and oxidative stress. Purified recombinant GhGLP2 exhibits superoxide dismutase (SOD) activity and inhibits spore germination of pathogens. Virus-induced silencing of GhGLP2 in cotton results in increased susceptibility to pathogens, plants exhibited severe wilt on leaves, enhanced vascular browning and suppressed callose deposition. Transgenic Arabidopsis (Arabidopsis thaliana) plants overexpressing GhGLP2 showed significant resistance to V. dahliae and F. oxysporum, with reduced mycelia growth, increased callose deposition and cell wall lignification at infection sites on leaves. The enhanced tolerance of GhGLP2-transgenic Arabidopsis to oxidative stress was investigated by methyl viologen and ammonium persulfate treatments, along with increased H(2)O(2) production. Further, the expression of several defense-related genes (PDF1.2, LOX2, and VSP1) or oxidative stress-related genes (RbohD, RbohF) was triggered by GhGLP2. Thus, our results confirmed the involvement of GhGLP2 in plant defense response against Verticillium and Fusarium wilt pathogens and stress conditions.